2015
DOI: 10.1111/ijfs.12913
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodology in β‐glucan wheat rolls production using microwave convection

Abstract: Summary The aim of research was to test the response surface methodology for optimising the β‐glucan content (BG) and microwave power (MV) during baking the wheat bread rolls. The increasing content of BG in wheat bread rolls caused the shortening the time of baking. The firmness of breadcrumbs was significantly influenced by the BG content in linear terms (P ≤ 0.05) and not influenced by the MV. The content of BG in the final product was highest in the products obtained with the middle range of MV. The respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A study by Kurek et al . () showed that the addition of β‐glucan in bread rolls had a significant influence on the bread firmness level. Also, the addition of pea flour to bread prepared with semolina was found to decrease bread firmness (Mastromatteo et al .…”
Section: Resultsmentioning
confidence: 99%
“…A study by Kurek et al . () showed that the addition of β‐glucan in bread rolls had a significant influence on the bread firmness level. Also, the addition of pea flour to bread prepared with semolina was found to decrease bread firmness (Mastromatteo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Physical properties were assessed to describe the quality of the baked gluten-free cake based on previous studies [ 3 , 23 ]. Texture profile analysis (TPA) was determined using a universal testing machine (Instron 5965; Instron, Canton, MA, USA) with Bluehill 2 software installed.…”
Section: Methodsmentioning
confidence: 99%
“…The response, or dependent, variables, were the quality characteristics of the muffins: firmness, springiness, chewiness, cohesiveness, and porosity. The significant terms in this model were found by the analysis of variance (ANOVA) for each response, the lack of fit, and coefficients of determination ( R 2 ), which were calculated to check the model accuracy (Kurek, Wyrwisz, & Wierzbicka, ).…”
Section: Methodsmentioning
confidence: 99%